2016
DOI: 10.1371/journal.pone.0164622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mannosidase and Trypsin Enzymes Effects on Biofilm Production of Pseudomonas aeruginosa Isolated from Burn Wound Infections

Abstract: Biofilm is an important virulence factor in Pseudomonas aeruginosa and has a substantial role in antibiotic resistance and chronic burn wound infections. New therapeutic agents against P. aeruginosa, degrading biofilms in burn wounds and improving the efficacy of current antimicrobial agents, are required. In this study, the effects of α-mannosidase, β-mannosidase and trypsin enzymes on the degradation of P. aeruginosa biofilms and on the reduction of ceftazidime minimum biofilm eliminating concentrations (MBE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
68
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 28 publications
13
68
4
Order By: Relevance
“…Data are representative of two independent experiments with 5 mice per group units of D-mannose, L-rhamnose, and D-glucose, where the individual -D-mannose residues are connected with linkages, suitable for digest by the identified via LC-MS/MS -mannosidases (e.g., Man2b1), we tested the importance of -mannosidases in regulating biofilm formation and bactericidal properties of neutrophils. Consistentwith recently published data by others,44 we observed that treatment with -mannosidase in vitro decreased P. aeruginosa biofilms.…”
supporting
confidence: 93%
“…Data are representative of two independent experiments with 5 mice per group units of D-mannose, L-rhamnose, and D-glucose, where the individual -D-mannose residues are connected with linkages, suitable for digest by the identified via LC-MS/MS -mannosidases (e.g., Man2b1), we tested the importance of -mannosidases in regulating biofilm formation and bactericidal properties of neutrophils. Consistentwith recently published data by others,44 we observed that treatment with -mannosidase in vitro decreased P. aeruginosa biofilms.…”
supporting
confidence: 93%
“…Cellulase has been used to inhibit biofilm formation by P. aeruginosa and S. aureus (Fleming et al, 2017). α-Mannosidase, β-mannosidase, PelA h , and PslG H have been found to have the same effect when used against P. aeruginosa (Baker et al, 2016, Banar et al, 2016. However, the application of AlsL, cellulase, α-mannosidase, β-mannosidase, PelA h , and PslG H against foodassociated bacteria is still limited.…”
Section: Alginate Lyasementioning
confidence: 99%
“…Therefore, the use of novel therapies that specifically disrupt biofilms within chronic wounds is a promising strategy for wound-care therapies. In this context, matrix-degrading enzymes have received particular attention and been used for the degradation of biofilm EPS [10][11][12][13][14][15]. However, the efficiency of each EPS-degrading enzyme will depend on the EPS composition [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Trypsin is a serine endoprotease that cleaves proteins or peptides and may depolymerize protein contents of bacterial biofilms. It has previously been shown that these two enzymes could disrupt in vitro mono-species biofilms of P. aeruginosa, S. aureus, Streptococcus pneumonia, and Staphylococcus epidermidis [10,15,16,29,30].…”
Section: Introductionmentioning
confidence: 99%